Losing Sonia - Franczak, Radka; Ackerman, Michael; Zbroniec-Zajt, Ita; Wydra, Anna; Szylak, Malgorzata (DOX, 2014)
The Documentary shows how a seemingly rigid monastery can be a place full of life, beauty and artistic expression. Sonia, a young nun, paints icons in the night and then sleeps until noon. She has a dog, cats, exotic birds, and a body that rebelled against the strict rigour of the monks. Trying to understand her and the meaning of her life choices, we come to Sonia’s family, marked with the history of Russia. At the same time, the film is a journey inside the Orthodox church, showing that the deep spirituality of the nation is being reborn. "Losing Sonia" tells the story of an unusual woman who, within the walls of the monastery, is trying to rebuild the values that Russian society has lost under successive political regimes. [www.wajdastudio.pl]
Keywords: DVD-Video